WHAT EXPLAINS VARIATIONS IN TRAINING ACROSS DIFFERENT NATIONAL CONTEXTS?THE CASE OF ABC PVT. LTD. - Naik, Vaidehi (2009)
This dissertation seeks to explore the effects of institutional configuration and form of capitalism prevalent in a nation on the organisational practices. For the purpose of the research a case study approach is used by taking a MNC in the ITES (Information Technology Enabled Services) sector. A MNC would help to gain an understanding of the unique institutions operating in a nation that will lead to dissimilar organisational practises in subsidiaries of the MNC. As globalisation has led to blurring of the political, social and economic boundaries of nation states and markets, it is important to know whether and to what extent the diverse institutions in a national context have a role to play in determining organisational practices or are multinational companies overtaking these institutions in regulating employment. This leads us to the further question of whether labour is deregulated and emergent economies is being protected or is being exploited by Multinationals to make the most of the competitive advantage gained by cheap labour and wages. The implication of rise in MNCs as a result of globalisation on the individual, organisation and society is also examined. The institutional theory and the Varieties of Capitalism literature was used to review the literature and the case study with the help of semi structured interviews and company documents helped establish convergence or divergence in findings with the existing literature. The research takes into account only one of the organisational practises that is ‘training’, which can help in broadening our understanding of the underlying issues. Taking only one practise would help in narrowing down the research area and making the study more specific. The Learning and Development manager together with two other associates in the Learning and Development department of the MNC were interviewed for the purpose of the study. Several factors seem to affect variation in practices of the subsidiaries of ABC which is taken as a case in point for the purpose of this study. The culture of the nation in which the MNC operates and the historical trajectory of the nation states seem to affect practises the most. But this variation in training was not very wide. The institutional configuration and the form of capitalism do not seem to have a major effect on organisational practices, as subsidiaries today choose the practices that are most beneficial to them and they have an intra organisational set up with rules and employment practices that are common across most subsidiaries. The role of the state institutions seems to be eroding and MNCs today have substantial power to determine their own employment practices which appear to be common across all subunits of the MNC. The attitude of the management of a subunit plays a vital role in establishing policies for the subsidiary. This is dependent on their values and beliefs which in turn are related to culture and this would seem to be the crucial factor determining variation in practices.